(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The results of the study showed that the consumption of carbohydrate and fat-rich products by workers of the mining and metallurgical plant is higher than the norm, while the consumption of milk and dairy products, fruits and vegetables, and fish is insufficient. Male workers consume more beef, chicken, cheese, and butter than women, which affects the overall energy and protein balance. It was found that the consumption level of dairy and dairy products is much lower than the physiological norm. High consumption of confectionery and sugar can lead to excess energy intake.